THE EFFECTIVENESS OF USING CAKE APPLICATION IN IMPROVING STUDENTS SPEAKING SKILLS - Octavianita, Ayu; Fitri, Nur Rizka; Rafinazly, Rafinazly; Ihsan, Muhammad Taufik (Education and Talent Development Center of Indonesia (ETDC Indonesia)., 2022)
Living on the era of globalization is inseparable to the advancement of technology. Technology has a huge impact on our daily life. It has, in fact, changed the way we live. There is no denying that technology plays a significant role in all aspects of life. All of our daily challenging duties can now be quickly and efficiently automated thanks to technology. Living has changed, and for the better, as a result of the application of technology. Learning and information exchange have become more interactive as a result of the introduction of technology in the educational area. The most significant impact of technology on education is the shift in our worldview. Technology is responsible for the tremendous shift in thinking from local to global. Since the advent of technology, the field of education (teaching and learning) has transformed. Schools have recognized the value of technology and have begun to incorporate it into the classroom. It has been easier for teachers to convey knowledge and for pupils to learn it with the introduction of computers in classrooms. The introduction of technology has improved the efficiency of teaching and learning. Cake application is one of the form of technology that is used in the education sector, Cake is a smartphone application that can help you learn to speak English. That application is simple to use and completely free. The goal of this research is to use a cake application to learn how to speak English in a classroom setting. As a research method, the researchers were obtained from literature of study review and fom other document analysis. The research question is: how is the Cake application for speaking English in online learning implemented? The study's findings show that students are interested in using the Cake application because it is simple to use and has numerous features that aid in improving speaking skills.